Integration of Remote Sensing Data and Geographic Information System for Mapping Landslide Risk Areas in Ambon City, Indonesia - Fekry Salim Hehanussa; Philia Christi Latue; Heinrich Rakuasa; Glendy Somae (Yayasan Adra Karima Hubbi, 2024)
This research investigates the integration of remote sensing data and Geographic Information Systems (GIS) to map landslide risk areas in Ambon City, Indonesia, a region characterized by its hilly terrain and susceptibility to landslides. Utilizing various environmental variables such as slope gradient, land use, and rainfall patterns, the study employs a multi-criteria approach to assess landslide vulnerability and distribution. The findings reveal significant correlations between anthropogenic factors, such as urbanization, and increased landslide risk, highlighting the urgent need for sustainable urban planning and disaster risk management strategies. By providing a comprehensive landslide risk map, this study aims to support local authorities in making informed decisions to enhance community resilience and mitigate the impacts of landslides in Ambon City.